FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT SISWA UNTUK MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI DI SMK NURUL FALAH PEKANBARU - Nikola Cliase Siregar; Suarman Suarman; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This reaearch aims to know the factors that influence students' interest in continuing their education to Higher Education at SMK Nurul Falah Pekanbaru. The population in this study was 103 students. The sample in this study was taken based on Slovin formula as many as 51 students, and using proportional random sampling technique. The type of data used in this study is primary data. Data collection techniques use data and documentation. Data analysis using descriptive analysis and multiple linear regression. Factors that influence interest consist of learning motivation factors, learning achievement, parents' socio-economic, peer environment. The results showed that both partially and simultaneously these factors had a significant effect on the interest in continuing education to Higher Education, meaning that the higher the student's learning motivation, the better the parents 'socio-economic, peer environment and student achievement, the higher the students' interest to continue education to Higher Education with a contribution of 92.9% and the remainder influenced by other factors not examined in this study including parenting, self potential, and information on Higher EducationKey Words: Learning Motivation, Learning Achievement, Parent Socio-Economic, Peer FriendEnvironment, Interest.